Характеристики цилиндрического индуктора вращающегося магнитного поля технологического назначения при его питании от сети с заданным напряжением - Милых, Владимир Иванович; Шилкова, Лариса Васильевна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Представлен расчетный анализ характеристик индуктора вращающегося магнитного поля технологического назначения. Конструкция его статора заимствована у трехфазного асинхронного двигателя. Цилиндрическая полость внутри статора занята рабочей камерой, в которую загружается сыпучее или жидкое обрабатываемое вещество. Обработка происходит движущимися с магнитным полем продолговатыми ферромагнитными элементами. Изложена методика получения электрических, магнитных и энергетических величин индуктора, основанная на численно-полевых расчетах с учетом магнитной анизотропии среды, заполняющей рабочую камеру. Взаимные зависимости ряда величин сформированы в семейство характеристик, проявляющих его свойства в рабочем режиме. В данной статье его особенностью является стабильность напряжения обмотки статора индуктора. Это дополняет проведенные ранее исследования индуктора в режиме со стабилизацией тока обмотки, что позволяет сравнить такие варианты работы. На примере тестового образца индуктора показан ряд его характеристик, приведены векторные диаграммы электрических и магнитных величин, иллюстрирующие их взаимные фазовые смещения.

A computational analysis of the characteristics of an inductor of a rotating magnetic field for technological purposes is presented. The design of its stator is borrowed from a three-phase induction motor. The cylindrical cavity inside the stator is occupied by a working chamber into which a granular or liquid processed substance is loaded. The processing is carried out with elongated ferromagnetic elements moving with a magnetic field. Problem. The purpose of the article is a study of the electromagnetic, phase, and energy characteristics of an inductor at its operation under load mode with a given voltage of the stator winding. Methodology. The study is performed on the basis of numerical calculations of the magnetic field, taking into account the anisotropy of the low-magnetic medium in the working chamber. Its discrete medium is represented homogeneous with different magnetic permeabilities on mutually perpendicular axes. The technique of transition from the results of the magnetic field calculation to the electric, magnetic, phase and energy parameters of the inductor is given. This is facilitated by the electrical equivalent circuit of the stator phase winding, the equilibrium equation of its electrical quantities, vector diagrams and an iterative method for determining the current at a given voltage. Results. Mutual dependencies of a number of inductor parameters are formed into a family of characteristics exhibiting its properties in an operating mode with a changing load. Characteristics include such quantities as magnetic flux linkage of the stator winding, its current and EMF, phase shifts between them, electromagnetic torque, expended and useful power and its losses, power factor and efficiency. In this article, a feature of this mode is the stability of the stator winding voltage in the inductor. This complements the earlier studies of the inductor in the mode with stabilization of the winding current, which allows to compare these options. On the example of a test sample of an inductor, a number of its characteristics are shown, vector diagrams of its electric and magnetic quantities illustrating their mutual phase shifts are given. Practical value. The presented technique for determining the electric and magnetic quantities of the inductor and their phase relationships, and also the shown family of characteristics can contribute to increasing the design efficiency and improving the inductors of the considered type. The developed technique has the universality property, as it is capable of displaying their various circuit and constructional design parameters.
Characteristics of a cylindrical inductor of a rotating magnetic field for technological purposes when it is powered from the mains at a given voltage
Keywords: ферромагнитные элементы; численно-полевые расчеты; магнитные поля; статоры; трехфазные цилиндрические индукторы; магнитная индукция; силовые линии; электромагнитные моменты; магнитные потокосцепления; фазные обмотки; фазовые смещения; three-phase cylindrical inductor; working chamber; ferromagnetic elements; rotating magnetic field; numerical calculations; load mode; stable voltage; phase shifts; magnetic parameters; energy parameters